KOMPARASI UPAH BORONGAN DAN UPAH HARIAN TERHADAP KINERJA - Queer, Wafa Almira; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to compare the performance of workers paid by the piece and the performance of those paid by hour. The research object is CV Albizzia Sinar Gemilang. This company applies two payment system to its workers. The respondents of this research are 83 production employees. The hypotheses of this research were tested using T test. This study finds different performance between workers paid by the piece and those paid by the hour. It advised that CV Albizzia Sinar Gemilang improve the performance of their employees and apply piece rate pay to all of its workers. Furthermore, the company is suggested to increase production supervision to improve the quality of its products.